Teachers' Perception toward Electronic Student Worksheet Based on Hand Washing Waste Treatment Projects to Improve Students' Creative Thinking Skills - Fachrunnisa*, Putri; Diawati, Chansyanah; Herlina, Kartini; Syafril, Syafrimen; Yusof, Rorlinda (Universitas Syiah Kuala, 2024)
Creative thinking skills are very important in the 21st century. This research aims to determine the perceptions of Natural Science teachers towards electronic student worksheets based on chicken manure waste processing projects to improve students' creative thinking abilities. This research uses mixed methods with a sequential explanatory design. Data was collected through questionnaires, then descriptive analysis was carried out. Questionnaires were distributed to 18 natural science teacher respondents and 115 junior high school students in Lampung Province. The research results show that 83% of teachers have not used project-based e-worksheets; 79% of teacher respondents have implemented Project Based Learning; while only 56% of teachers have not carried out creative thinking ability tests. Based on student response questionnaires, 82% of teachers have given project assignments, but these projects are not based on real problems in the environment. The survey results show that 86% of teacher respondents already know about creative thinking skills, but the indicators of creative thinking skills that teachers understand are different from the indicators of creative thinking skills that should be measured. Based on the research results, it can be concluded that e-worksheets based on chicken waste processing projects are needed to improve students' creative thinking abilities